Selection of a Bacillus pumilus Strain Highly Active against Ceratitis capitata (Wiedemann) Larvae - Molina, C. Alfonso (American Society for Microbiology (ASM), 2010)
Ceratitis capitata (Wiedemann) (Diptera: Tephritidae), the Mediterranean fruit fly (medfly), is one of the most important fruit pests worldwide. The medfly is a polyphagous species that causes losses in many crops, which leads to huge economic losses. Entomopathogenic bacteria belonging to the genus Bacillus have been proven to be safe, environmentally friendly, and cost-effective tools to control pest populations. As no control method for C. capitata based on these bacteria has been developed, isolation of novel strains is needed. Here, we report the isolation of 115 bacterial strains and the results of toxicity screening with adults and larvae of C. capitata. As a result of this analysis, we obtained a novel Bacillus pumilus strain, strain 15.1, that is highly toxic to C. capitata larvae. The toxicity of this strain for C. capitata was related to the sporulation process and was observed only when cultures were incubated at low temperatures before they were used in a bioassay. The mortality rate for C. capitata larvae ranged from 68 to 94% depending on the conditions under which the culture was kept before the bioassay. Toxicity was proven to be a special characteristic of the newly isolated strain, since other B. pumilus strains did not have a toxic effect on C. capitata larvae. The results of the present study suggest that B. pumilus 15.1 could be considered a strong candidate for developing strategies for biological control of C. capitata.